Economic statecraft : human rights, sanctions, and conditionality - Fabre, Cécile (Harvard University Press, 2018)
Leaders have used economic power as a tool of foreign policy since at least Pericles, whose trade sanctions against Megara helped to spark the Peloponnesian War. But as Cécile Fabre notes, philosophers have spent relatively little time thinking about the relevant ethics, especially compared with the time they have spent thinking about the ethics of war. Yet the moral questions raised by the use of economic statecraft are significant and complex. Fabre deploys a cosmopolitan theory of justice and the theory of justified harm to answer these questions, and concludes that political actors are morally entitled to resort to economic sanctions and conditional aid, but only as a means to protect human rights, and so long as the harms which they thereby inflict are not out of proportion to the goods they bring about. Moreover, they are morally entitled to resort to conditional lending and conditional debt forgiveness, not just with a view to protect human rights, but also, under certain conditions, to pursue other non-wrongful political goals.--